Dynamic gut microbiome-metabolome in cationic bovine serum albumin induced experimental immune-complex glomerulonephritis and effect of losartan and mycophenolate mofetil on microbiota modulation - Wenying Shi; Zhaojun Li; Weida Wang; Xikun Liu; Haijie Wu; Xiaoguang Chen; Xunrong Zhou; Sen Zhang (Elsevier, 2024)
Dynamic changes in gut dysbiosis and metabolomic dysregulation are associated with immune-complex glomerulonephritis (ICGN). However, an in-depth study on this topic is currently lacking. Herein, we report an ICGN model to address this gap. ICGN was induced via the intravenous injection of cationized bovine serum albumin (c-BSA) into Sprague-Dawley (SD) rats for two weeks, after which mycophenolate mofetil (MMF) and losartan were administered orally. Two and six weeks after ICGN establishment, fecal samples were collected and 16S ribosomal DNA (rDNA) sequencing and untargeted metabolomic were conducted. Fecal microbiota transplantation (FMT) was conducted to determine whether gut normalization caused by MMF and losartan contributed to their renal protective effects. A gradual decline in microbial diversity and richness was accompanied by a loss of renal function. Approximately 18 genera were found to have significantly different relative abundances between the early and later stages, and Marvinbryantia and Allobaculum were markedly upregulated in both stages. Untargeted metabolomics indicated that the tryptophan metabolism was enhanced in ICGN, characterized by the overproduction of indole and kynurenic acid, while the serotonin pathway was reduced. Administration of losartan and MMF ameliorated microbial dysbiosis and reduced the accumulation of indoxyl conjugates in feces. FMT using feces from animals administered MMF and losartan improved gut dysbiosis by decreasing the Firmicutes/Bacteroidetes (F/B) ratio but did not improve renal function. These findings indicate that ICGN induces serous gut dysbiosis, wherein an altered tryptophan metabolism may contribute to its progression. MMF and losartan significantly reversed the gut microbial and metabolomic dysbiosis, which partially contributed to their renoprotective effects.